Differences in aerosol output and airways responsiveness between the DeVilbiss 40 and 45 hand held nebulisers. Issue 6 (June 1995) - Hartley-Sharpe, C J; Booth, H; Johns, D P; Walters, E H
Abstract : BACKGROUND--The DeVilbiss 40 glass hand held nebulisers have been widely used for airways responsiveness testing in epidemiological surveys of asthma. These nebulisers have been superseded in some recent studies by the DeVilbiss 45 plastic hand held nebulisers with the assumption that they are interchangeable. This study compared the aerosol outputs of the DeVilbiss 40 and DeVilbiss 45 nebulisers and investigated whether there was any difference in the in vivo measurements of airways responsiveness when using the two nebuliser types. METHODS--The aerosol output of six DeVilbiss 40 and six DeVilbiss 45 nebulisers was calculated by weight loss per actuation, the usual method of calibrating nebuliser output, and compared with the true amount of aerosol obtained measured by a flouride tracer technique. Airways responsiveness was measured twice in 13 asthmatic patients under identical conditions by the Yan protocol using DeVilbiss 40 and 45 nebulisers in random order. RESULTS--Weight loss overestimated the true aerosol output of both types of nebulisers. Weight loss was similar for the DeVilbiss 40 and 45 nebulisers but the true aerosol output of the DeVilbiss 45 was nearly twice that of the DeVilbiss 40 nebuliser. The geometric mean PD20 values with the DeVilbiss 40 nebuliser was a mean 1.7 doubling doses of histamine higher than that obtained with the DeVilbiss 45 nebuliser. CONCLUSIONS--The DeVilbiss 40 and 45 nebulisers should not be used interchangeably for airways responsiveness testing merely because their outputs based on weight loss are similar. Artefactual differences in the prevalence rates of airways responsiveness could occur in longitudinal studies if a change was inadvertently made from using DeVilbiss 40 to DeVilbiss 45 nebulisers.